Identification of expandable human hepatic progenitors which differentiate into mature hepatic cells in vivo. Issue 7 (10th June 2005) - Nowak, G; Ericzon, B-G; Nava, S; Jaksch, M; Westgren, M; Sumitran-Holgersson, S
Abstract : Background: Liver diseases include a wide spectrum of both acute and chronic conditions which are associated with significant morbidity and mortality worldwide. Hepatocyte transplantation has therapeutic potential in the treatment of liver diseases, but its clinical use is hampered by the lack of donor tissue. Generation of hepatocytes in vitro from adult or fetal liver cell progenitors or, alternatively, identification of a progenitor population which in vivo can generate mature liver cells could solve this problem. Methods: CD117+/CD34+/Lin− human fetal liver cells were isolated by magnetic cell sorting and expanded in culture. Both freshly isolated and in vitro expanded cells in various passages were studied for their ability to be functional in hepatic parenchyma following d -galactosamine (GalN) induced injury in nude C57 black mice. Results: Freshly isolated and in vitro expanded CD117+/CD34+/Lin− cells, when transplanted intrasplenically into GalN treated mice, morphologically and functionally differentiated into hepatocytes and cholangiocytes. Human specific albumin, α fetoprotein, cytokeratin 19, and antitrypsin mRNA were expressed in mouse liver. In addition, the human progenitor cells expressed glucose-6-phosphatase, glycogen, albumin, gamma glutamyl transpeptidase, and dipeptidyl peptidase IV after transplantation. Expanded cells in various passages maintained their capacity to differentiate into functional liver cells. Conclusions: Fetal liver CD117+/CD34+/Lin− progenitors and their progeny proliferated in vitro and also functionally differentiated into mature hepatic cells in an acute liver injury model. Successful in vitro expansion of liver progenitor cells provides a basis for developing cell therapy strategies, metabolic and toxicity testing systems, and may serve as a vehicle for gene therapy.